REFORMASI PENDIDIKAN MENUJU INDONESIA BARU - Khoirunnisaa' Khoirunnisaa' (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2017)
The existing education in Indonesia still has relevance to the history of Indonesian education development. Even the existence of educational reform is a historical demand with the meaning that the history of Indonesia's education had experienced the golden age, with the spirit of nationalism, patriotism and so on. Therefore, education to new Indonesia requires actions that can bring about changes by reviewing the education system by: 1). Internal change is to restore full educational functions or restoring pedagogical autonomy to schools and teachers. 2). External change is to make the education system an integral part of economic reform, politics, law and other reforms that will occur in society.